Availability, effectiveness and safety of ART in sub-Saharan Africa: a systematic review. Issue 2 (26th March 2018) - Botha, Barend; Shamley, Delva; Dyer, Silke
Abstract: STUDY QUESTION: What is the evidence pertaining to availability, effectiveness and safety of ART in sub-Saharan Africa? SUMMARY ANSWER: According to overall limited and heterogeneous evidence, availability and utilization of ART are very low, clinical pregnancy rates largely compare to other regions but are accompanied by high multiple pregnancy rates, and in the near absence of data on deliveries and live births the true degree of effectiveness and safety remains to be established. WHAT IS KNOWN ALREADY: In most world regions, availability, utilization and outcomes of ART are monitored and reported by national and regional ART registries. In sub-Saharan Africa there is only one national and no regional registry to date, raising the question what other evidence exists documenting the status of ART in this region. STUDY DESIGN, SIZE, DURATION: A systematic review was conducted searching Pubmed, Scopus, Africawide, Web Of Science and CINAHL databases from January 2000 to June 2017. A total of 29 studies were included in the review. The extracted data were not suitable for meta-analysis. PARTICIPANTS/MATERIALS, SETTING, METHODS: The review was conducted according to Preferred Reporting Items for Systematic Reviews (PRISMA) guidelines. All peer-reviewed manuscripts irrespective of language or study design that presented original data pertaining to availability, effectiveness and safety of ART in sub-Saharan Africa were eligible for inclusion. Selection criteria were specified prior to the search. Two authors independently reviewed studies for possible inclusion and critically appraised selected manuscripts. Data were analysed descriptively, being unsuitable for statistical analysis. MAIN RESULTS AND THE ROLE OF CHANCE: The search yielded 810 references of which 29 were included based on the predefined selection and eligibility criteria. Extracted data came from 23 single centre observational studies, two global ART reports, two reviews, one national data registry and one community-based study. ART services were available in 10 countries and delivered by 80 centres in six of these. Data pertaining to number of procedures existed from three countries totalling 4619 fresh non-donor aspirations in 2010. The most prominent barrier to access was cost. Clinical pregnancy rates ranged between 21.2% and 43.9% per embryo transfer but information on deliveries and live births were lacking, seriously limiting evaluation of ART effectiveness. When documented, the rate of multiple pregnancy was high with information on outcomes similarly lacking. LIMITATIONS, REASONS FOR CAUTION: The findings in this review are based on limited data from a limited number of countries, and are derived from heterogeneous studies, both in terms of study design and quality, many of which include small sample sizes. Although representing best available evidence, this requires careful interpretation regarding the degree of representativeness of the current status of ART in sub-Saharan Africa. WIDER IMPLICATIONS OF THE FINDINGS: The true extent and outcome of ART in sub-Saharan Africa could not be reliably documented as the relevant information was not available. Current efforts are underway to establish a regional ART data registry in order to report and monitor availability, effectiveness and safety of ART thus contributing to evidence-based practice and possible development strategies. STUDY FUNDING/COMPETING INTERESTS: No funding was received for this study. The authors had no competing interests. TRIAL REGISTRATION NUMBER: PROSPERO CRD42016032336